Salah Satu Bentuk Perlindungan Bagi Penyandang Disabilitas Mental Sebuah Studi Eksplorasi Peraturan Perundang-Undangan Indonesia tentang Perlindungan Hak Waris Penyandang Disabilitas Mental: One Form of Protection for Persons with Mental Disabilities: An Exploration Study of Indonesian Legislations on the Protection of Inheritance Rights of Persons with Mental Disabilities - Rizka Rizka; Anindia Fadhilah (Society, 2022)
Indonesia ratified the Convention on the Rights of Persons with Disabilities (CRPD) and enacted Laws that provide for the right to justice and legal protection for persons with mental disabilities, including the right to own and inherit a legacy. Paradoxically, the same laws legalize actions that undermine their rights. This study examines the legal protection accorded to persons with mental/intellectual disabilities over their inheritance rights as per the Indonesian three-pronged inheritance laws comprising Islamic law, adat law and the civil code. This research is descriptive, using a normative approach with a measure of doctrinal research. Indonesian laws still provide for substituted decision-making for persons with mental disabilities, which legalizes denying their right to legal agency. Ambiguities abound in the laws on important aspects, like how one is declared incapable of making legal decisions. Supported decision-making mechanisms for persons with mental disabilities in Indonesian laws would provide the basis for setting up support centers where persons with mental disabilities can access the necessary support to enable them to make legal decisions. This study can be useful in addressing issues that infringe on the legal rights and protections of people with mental disabilities.